D-Cycloserine acts via increasing the GluN1 protein expressions in the frontal cortex and decreases the avoidance and risk assessment behaviors in a rat traumatic stress model - CABADAK, HÜLYA; GÖREN, MEHMET ZAFER (ELSEVIER SCIENCE BV, 2015)
D-cycloserine (DCS), an FDA approved anti-tuberculosis drug has extensively been studied for its cognitive enhancer effects in psychiatric disorders. DCS may enhance the effects of fear extinction trainings in animals during exposure therapy and hence we investigated the effects of DCS on distinct behavioral parameters in a predator odor stress model and tested the optimal duration for repeated daily administrations of the agent. Cat fur odor blocks were used to produce stress and avoidance and risk assessment behavioral parameters were used where DCS or saline were used as treatments in adjunct to extinction trainings. We observed that DCS facilitated extinction training by providing further extinction of avoidance responses, risk assessment behaviors and increased the contact with the cue in a setting where DCS was administered before extinction trainings for 3 days without producing a significant tolerance. In amygdala and hippocampus, GluN1 protein expressions decreased 72 h after the fear conditioning in the traumatic stress group suggesting a possible down-regulation of NMDARs. We observed that extinction learning increased GluN1 proteins both in the amygdaloid complex and the dorsal hippocampus of the rats receiving extinction training or extinction training with DCS. Our findings also indicate that DCS with extinction training increased GluN1 protein levels in the frontal cortex. We may suggest that action of DCS relies on enhancement of the consolidation of fear extinction in the frontal cortex. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Amygdaloid complex; Dorsal hippocampus; Predator scent test; Post-traumatic stress disorder; FEAR-POTENTIATED STARTLE; MEDIAL PREFRONTAL CORTEX; PLACEBO-CONTROLLED TRIAL; CONDITIONED FEAR; EXPOSURE THERAPY; GLUTAMATE RECEPTORS; CAT ODOR; EXTINCTION; MEMORY; FACILITATION